Association of Anxiety, Depression, and Body Image Disorder with Pain-Related Disability in Post-Mastectomy Breast Cancer Patients - Mohammad Aryaie; Danial Bagheri; Rahman Berdi Ozouni-Davaji; Sima Mostafshar; Eftekhar Bolukat; Reza Khodabakhshi (Golestan University Of Medical Sciences, 2017)
Introduction: Breast cancer and its treatment have notable adverse effects on patients’ body image, which could result in disability and psychological distress. Therefore, the present study investigated the association of anxiety, depression, and body image disorder with pain-related disability in post-mastectomy female breast cancer patients. Materials and Methods: This cross-sectional study was conducted on 137 post-mastectomy female breast cancer patients referred to two hospitals in Tehran, in 2015. Demographic data were collected, and all subjects completed questionnaires for patients with cancer, pain disability index and hospital anxiety and depression scale. Validity and reliability of all questionnaires used in the study had been verified previously.Results: There were significant inverse correlations between depression and body image (r=-0.24, P<0.01), anxiety and pain related disability (r=0.25, P<0.01), and body image and pain-related disability (r=0.47, P<0.001). Multiple regression analysis showed that anxiety (B=0.29, CI=0.97-3.94) and body image disorder (B=0.53, CI=0.81-1.62) were significantly correlated with pain-related disability after adjusting the age of patients and treatment period. Conclusions: Body image and anxiety are significantly correlated with pain-related disability. In addition, there is a significant correlation between body image and depression in post-mastectomy patients. Thus, anxiety and body image could be considered as risk factors of pain-related disability regardless of the treatment course and demographic variables. Identification of breast cancer patients with psychological disorders and disturbed body image seems beneficial for preventing pain-related disability after mastectomy.